Risk of Long COVID in hospitalized individuals treated with remdesivir for acute COVID-19 - Mark Berry; Amanda M. Kong; Roger Paredes; Julie Paone; Rohan Shah; Rebecca Taylor; Essy Mozaffari; Rikisha Gupta; Robert L. Gottlieb; Lourdes Mateu; Mazin Abdelghany; Jason D. Goldman; et al. (Scientific Reports)
Abstract Long COVID comprises a multisystem syndrome occurring after COVID-19. This retrospective cohort study investigated whether remdesivir given during acute COVID-19 is associated with reduced incidence of Long COVID, including in immunocompromised subgroups. The HealthVerity database of hospital chargemaster data linked to closed claims was queried for patients aged ≥ 12 years hospitalized for ≥ 2 days with COVID-19 between May 1, 2020, and September 30, 2021. Relative risk between remdesivir-exposed and unexposed patients was calculated for 16 individual Long COVID outcomes and a composite of any Long COVID outcome, occurring 90–270 days after hospital admission. Subgroup analyses occurred in immunocompromised patients. Regression models accounted for censoring, competing risks, and treatment assignment weights; statistical inferences were adjusted for multiple comparisons. Among 3,661,303 hospitalized patients, 52,006 with COVID-19 were included; 20,246 (38.9%) were immunocompromised. In the overall and immunocompromised populations, respectively, 33.0% and 29.5% received remdesivir; the composite of ≥ 1 Long COVID outcome occurred in 55.5% and 62.9%. Patients administered remdesivir experienced lower risk of any Long COVID outcome (risk ratio, 0.96; 95% CI 0.94–0.97; adjusted P < 0.001). Risk for several individual Long COVID outcomes was lower in those receiving remdesivir in the overall and immunocompromised populations. In conclusion, exposure to remdesivir was associated with a lower risk of Long COVID.